Managing educational resource-student information systems using BVAGQ fragmented database replication model - Noraziah, Ahmad; Ainul Azila, Che Fauzi; Mustafa, Mat Deris; Md Yazid, Mohd Saman; Noriyani, Mohd Zin; Khan, Nawsher (Elsevier Ltd., 2011)
Significant and urgent solutions are required in order to manage educational resource efficient and effective. Data replication is one of the key components to manage the huge of resources in data grid architecture as it enhances data access and reliability. Replication provides user with fast, local access to shared data, and increased availability of applications because alternate data access options exist. In this paper, we present on how to manage fragmented database replication and transaction for educational resources-Student Information System (SIS) by using Binary Vote Assignment on Grid Quorum (BVAGQ) fragmented database replication model. Furthermore, fragmentation in distributed database is very useful in terms of usage, reliability and efficiency. In particular, BVAGQ able to partition the database into disjoint fragments. The result shows that managing replication and transaction through proposed BVAGQ able to preserve data availability and consistency. It also increases the degrees of parallelism. This is because by using fragmentation, replication and transaction can be divided into several subqueries that operate on the fragments.